Modelling dynamics of transmission conductors with Cosserat rod - Xiong, Hui; Li, Zheng-liang; Chang, Jian; You, Lihua; Zhang, Jian J.; Wang, Meili (Computer Assisted Methods in Engineering and Science; Vol 20 No 1 (2013), 2017)
We proposed a method to analyze the galloping, a vibration by wind force, of transmission conductors. The Cosserat rod model was introduced to describe the motion of the conductor line. The deformation was tracked using the intrinsic framework of material coordinates which are able to handle the large motion in galloping phenomena. The Cosserat model provided a theory framework to simulate the non-linear coupling of the torsional motion and the translational motion. Such non-linear coupling was reported as one of the main causes for the galloping phenomena.